Impacts of Foreign Employment on People’s Lifestyles in Diktel Rupakot Majhuwagadhi Municipality - Rai, Shyam Kumar (DMC Journal, 2024)
This study has been carried out to explore the relevancy and rationale of foreign employment that has affected to society. Due to the fast technological changes, bilateral agreements between countries and diplomatic relations among countries have brought changes in the trend of foreign employment. So, this paper aims to explore the impacts of foreign employment on people’s lifestyles relating to the current situation and to find differences between now and then along with the utilization of remittances. The target population was selected from Diktel Rupakot Majhuwagadhi Municipality ward no. 2 and 10. The sample size was 20 altogether. A purposeful sampling method was applied to select the sample size. Semi-structured questionnaires, focused group discussions, field visits and observation were administered to collect the data from the informants. The mixed method is implemented in this study. Previous literature and current practices of foreign employment methodologically have been analyzed. The findings show that informants' overall perception of foreign employment's impacts on people’s lifestyles is positive. The remittance support system for society has been found effective. On the other hand, the divorce between husband and wife, blaming unethical character to the woman by the community whose husband has migrated for foreign job, and children being without the support of father and mother are some of the few negative consequences of foreign employment.